The Effect of Drying Time on the Antioxidant Properties of Single Black Garlic Powder - Sari, Rika; Herdyastuti, Nuniek (Jurnal Pijar Mipa, 2024)
Black garlic is a processed product derived from fresh garlic that generally has a taste and aroma that is less preferred. A drying process is employed to increase the attractiveness of consuming black garlic. This study aims to assess the impact of the drying time on the antioxidant activity and content of antioxidant compounds such as phenolics, flavonoids, and tannins in single black garlic. The drying time is expected to yield a single black garlic powder that is more convenient for consumption, whether in capsule form or as an addition to food products. With low moisture content, single black garlic powder has a longer shelf life and high antioxidant activity, potentially commanding a higher market value. In this research, the drying time was carried out on a single black garlic using an oven for 6, 12, 18, and 24 hours. The analysis of the total phenolic content (TPC), entire tannin content (TTC), and total flavonoid content (TFC) was determined using a Uv-Vis spectrophotometer, and each component was measured concerning gallic acid equivalent for TPC, quercetin for TFC, and tannic acid for TTC. Antioxidant activity was determined using the DPPH method, and the outcomes were expressed as IC50 values. The research shows that the extended drying time leads to an augmentation of the antioxidant compound in black garlic. Drying for 24 hours produces significant outcomes, showing potent antioxidant activity with an IC50 value of 37,019 ppm (powerful antioxidant category), total phenolic content value is 44,785 ± 0,033 mgGAE/g, total flavonoid content value is 32,033 ± 0,008 mgQE/g, and total tannins content value is 74,884 ± 0,057 mgTAE/g. Statistical analysis using a one-way ANOVA showed a significant influence of drying time on TPC, TFC, and TTC (p < 0,05). The longer the drying time, the higher the antioxidant activity and the content of compounds acting as antioxidants in black garlic powder.